Spirituality of the Celebration of the Eucharist - Dziuba, Adndrzej (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
The Eucharist is a dynamic, sacramental love offered for a faith-living person, even its foundation, and remains a subject worthy of scientific reflection. For the community it is the heart of the life of faith as the “communion” and builds up the Church — the Body of Christ. The Eucharist is the food, the bread of pilgrims, for the spiritual life of all believers. To refuse to eat the Eucharistic Bread can lead to difficulties and even to the loss of faith. That is why we need to be ready to gather at the Eucharist, in which we listen to the Word and break the bread. These experiences are preceded by initial act of penance, whose signs also appear later in the liturgy. This allows us to understand more deeply that we share in the memory of Christ's Eucharistic Sacrifice. The Church offers constant thanksgiving for the People of the New Covenant, knowing in faith that it is the Paschal Sacrifice of Christ. At the end of the celebration, the joy of the accomplished work of love is filled with adoration marked also by silence.